(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The status of women in Late Antiquity and early Christianity has been an inspiring theme for debate in the last few decades. The New Testament is full of texts that testify about the involvement of women in early Christian communities. In the Epistles of St. Paul, he salutes women, addresses them as collaborators, one of them as the deaconess, and even calls one the Apostle. This text makes a brief overview of the role and position of women in antiquity, which, in addition to the later analysis of their place in the early Christian world, will best show whether and how much the new religion influenced their, to use here an exquisite modern word, emancipation. In the context of this, we are also going to study several examples of deciduous mosaics from archaeological sites in the Republic of Macedonia.